Synchrotron X-ray diffraction to understand crystallographic texture of enamel affected by Hunter syndrome. (August 2017) - Khan, Malik Arshman; Addison, Owen; James, Alison; Hendriksz, Christian J.; Al-Jawad, Maisoon
Highlights: Synchrotron X-ray diffraction is a state-of-the-art technique that has been used to determine the orientation of enamel crystallites. Enamel in hunter syndrome has poor crystallite organization. In Hunter syndrome, the organization of crystallites at the enamel incisal surface is less affected when compared to bulk and cervical enamel. Abstract: Objective: To determine whether Hunter syndrome (MPS II) affects the crystallographic texture (preferred orientation) of enamel. Design: Synchrotron X-ray diffraction, being a state of the art technique, has been used to determine the enamel crystallite orientation in enamel affected by Hunter syndrome (MPS II). The incisal, lingual and cervical regions of the MPS II affected tooth were observed and compared to healthy tooth. Results: It was observed that there is a loss of organization of crystallites in deciduous incisal enamel affected by Hunter syndrome (MPS II) as compared to healthy deciduous enamel tissue. Generally it was observed that, in contrast to the healthy enamel, the enamel affected by MPS II possessed a lower crystallographic preferred orientation, with a more uniform spatial distribution; however, the enamel at the incisal tip was relatively unaffected. Conclusion: Hunter syndrome affects the enamel texture in the lingual and cervical regions of the tooth.